A computer‐guided quality improvement tool for primary health care: cost‐effectiveness analysis based on TORPEDO trial data. Issue 2 (27th June 2020) - Patel, Bindu; Peiris, David P; Patel, Anushka; Jan, Stephen; Harris, Mark F; Usherwood, Tim; Panaretto, Kathryn; Lung, Thomas
Abstract: Objective: To assess the cost‐effectiveness of a computer‐guided quality improvement intervention for primary health care management of cardiovascular disease (CVD) in people at high risk. Design: Modelled cost‐effectiveness analysis of the HealthTracker intervention and usual care for people with high CVD risk, based on TORPEDO trial data on prescribing patterns, changes in intermediate risk factors (low‐density lipoprotein cholesterol, systolic blood pressure), and Framingham risk scores. Participants: Hypothetical population of people with high CVD risk attending primary health care services in a New South Wales primary health network (PHN) of mean size. Intervention: HealthTracker, integrated into health care provider electronic health record systems, provides real time decision support, risk communication, a clinical audit tool, and a web portal for performance feedback. Main outcome measures: Incremental cost‐effectiveness ratios (ICERs): difference in costs of the intervention and usual care divided by number of CVD events averted with HealthTracker. Results: The estimated numbers of major CVD events over five years per 1000 patients at high CVD risk were lower in PHNs using HealthTracker, both for patients with prior CVD events (secondary prevention; 259 v 267 with usual care) and for those without prior events (primary prevention; 168 v 176). Medication costs were higher and hospitalisation costs lower with HealthTracker than with usual care for both primary and secondary prevention. The estimated ICER for one averted CVD event was $7406 for primary prevention and $17 988 for secondary prevention. Conclusion: Modelled cost‐effectiveness analyses provide information that can assist decisions about investing in health care quality improvement interventions. We estimate that HealthTracker could prevent major CVD events for less than $20 000 per event averted. Trial registration (TORPEDO): Australian New Zealand Clinical Trials Registry, ACTRN 12611000478910.